Dramatopisarki w natarciu — feministyczny charakter najnowszej dramaturgii rosyjskojęzycznej - Charko-Klekot, Paulina (Rusycystyczne Studia Literaturoznawcze, 2020)
This article enumerates the most salient features of works by the youngest contemporary Russian-speaking playwrights of Eastern Europe, including Irina Vaskovska, Asya Voloshyna, Natalya Blok, Olga Shilyayeva and Darya Slyusarenko. Conducted from a feminist perspective, the study discusses various ways in which the plays contradict a male-centric vision of the world. Their authors undertake the (re-)definition of the concept of femininity by proposing new perspectives on seemingly well-known topics such as motherhood, family relationships, sexuality, and corporeality. The protagonists of the plays presented in the text oppose the social and moral norms that limit them, make attempts to go beyond those cliches, and fight for the opportunity to be themselves.